Modelling the Impact of Bottlenecks on Arterial Travel Time Using Neural Networks - Abdallah, Azza (2012)
A Master of Science thesis in Civil Engineering by Azza Abdallah entitled, "Modelling the Impact of Bottlenecks on Arterial Travel Time Using Neural Networks," submitted in June 2012. Thesis advisor is Dr. Ghassan Abu-Lebdeh. Soft and hard copy available.